2019
DOI: 10.1631/jzus.b1900195
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of methane-rich saline on mice with allergic asthma by inhibiting inflammatory response, oxidative stress and apoptosis

Abstract: Background: Asthma is a common cause of breathing difficulty in children and adults, and is characterized by chronic airway inflammation that is poorly controlled by available treatments. This results in severe disability and applies a huge burden to the public health system. Methane has been demonstrated to function as a therapeutic agent in many diseases. The aim of the present study was to explore the effect of methane-rich saline (MRS) on the pathophysiology of a mouse model of asthma and its underlying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Asthma is a chronic respiratory disease with various clinical and pathophysiological profiles including increased mucus secretion, narrowing of the airways, reversible bronchial obstruction, goblet cell hyperplasia, airway hyper responsiveness (AHR), as well as identified acute and chronic inflammation [ 1 , 2 ]. In addition to the aforementioned disease characteristics, asthma has recently been defined as a heterogeneous disease or complex syndrome and can be classified into several phenotypes and endotypes, each with specific clinical and pathological attributes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is a chronic respiratory disease with various clinical and pathophysiological profiles including increased mucus secretion, narrowing of the airways, reversible bronchial obstruction, goblet cell hyperplasia, airway hyper responsiveness (AHR), as well as identified acute and chronic inflammation [ 1 , 2 ]. In addition to the aforementioned disease characteristics, asthma has recently been defined as a heterogeneous disease or complex syndrome and can be classified into several phenotypes and endotypes, each with specific clinical and pathological attributes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation of the airways is associated with the reaction of various immune cells and different mediators [ 11 ]. They secrete several immune cells, including T helper 2 cells (Th2), mast cells, eosinophils, airway epithelial cells, cytokines, chemokines, and inflammatory mediators that damage lung tissue [ 2 ]. Th2 lymphocytes produce cytokines such as interleukins-4, 5, and 13 (IL-4, IL-5, IL-13, respectively), leading to the production of immunoglobulin E , mucosal metaplasia, and increased production of eotaxins and eosinophils in the airways [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methane possesses antioxidative, anti-inflammatory, and antiapoptotic properties, which have been proved through a septic mouse model [13]. Furthermore, methane exhibited good effects on sepsis-induced mice kidney injury, intestinal IR injury, and liver IRI [8, 12].…”
Section: Discussionmentioning
confidence: 99%
“…The methane saline was produced as previously described which was freshly prepared 1 day before experiments to ensure a steady concentration [12]. The concentration of MRS was 1.2-1.5 mmol/L which was detected by using gas chromatography as the previous study [13].…”
Section: Methodsmentioning
confidence: 99%
“…The myocardial OxPhos capacity was more preserved and cytochrome c release was decreased as a result of CH 4 -enriched storage, with the relative mRNA expression for hypoxia-and ER stress-associated genes (including HIF-1α) also being significantly reduced (Benke et al, 2021). Indeed, several previous studies demonstrated that exogenous CH 4 modulates the intrinsic, mitochondrial pathway of pro-apoptotic activation in model experiments (Ye et al, 2015;Chen et al, 2016;Liu et al, 2016;Jia et al, 2018) and CH 4 administration exhibited anti-apoptotic effects and protected the pulmonary epithelial cells in a murine model of ovalbumin-induced allergic asthma as well (Zhang et al, 2019). More importantly, the anti-apoptotic properties of CH 4 inhalation were associated with improved pulmonary compliance and surfactant production in a rodent model of lung IR injury (Zhang et al, 2021).…”
Section: Inhaled Chmentioning
confidence: 94%